Clinical variability at the mild end of BRAT1‐related spectrum: Evidence from two families with genotype–phenotype discordance. Issue 1 (15th November 2021) - Nuovo, Sara; Baglioni, Valentina; De Mori, Roberta; Tardivo, Silvia; Caputi, Caterina; Ginevrino, Monia; Micalizzi, Alessia; Masuelli, Laura; Federici, Giulia; Casella, Antonella; Lorefice, Elisa; Anello, Danila; et al.
Abstract: Biallelic mutations in the BRAT1 gene, encoding BRCA1‐associated ATM activator 1, result in variable phenotypes, from rigidity and multifocal seizure syndrome, lethal neonatal to neurodevelopmental disorder, and cerebellar atrophy with or without seizures, without obvious genotype–phenotype associations. We describe two families at the mildest end of the spectrum, differing in clinical presentation despite a common genotype at the  BRAT1 locus. Two siblings displayed nonprogressive congenital ataxia and shrunken cerebellum on magnetic resonance imaging. A third unrelated patient showed normal neurodevelopment, adolescence‐onset seizures, and ataxia, shrunken cerebellum, and ultrastructural abnormalities on skin biopsy, representing the mildest form of NEDCAS hitherto described. Exome sequencing identified the c.638dup and the novel c.1395G>A BRAT1 variants, the latter causing exon 10 skippings. The p53‐MCL test revealed normal ATM kinase activity. Our findings broaden the allelic and clinical spectrum of BRAT1 ‐related disease, which should be suspected in presence of nonprogressive cerebellar signs, even without a neurodevelopmental disorder.